Successful Primary Treatment of a Hydatidiform Mole with Methotrexate and EMA/CO - M. De Vos; M. Leunen; C. Fontaine; Ph. De Sutter (Case Reports in Medicine)
Background. The preferred treatment method of most hydatidiform moles is suction aspiration. In rare circumstances uterine abnormalities may preclude surgical treatment. Case. We report a case of complete molar pregnancy successfully treated with methotrexate followed by EMA/CO. A 38-year-old woman with a complete hydatidiform mole and multiple uterine fibroids underwent a failed attempt at suction aspiration. Following treatment with methotrexate, a nonmetastatic persistent trophoblastic tumour developed. Six cycles of EMA/CO led to complete remission. Conclusion. We propose that primary treatment of molar pregnancies with chemotherapy is a useful treatment option in cases where uterine abnormalities interfere with suction aspiration.